1985
DOI: 10.1083/jcb.101.2.454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TPA on ion fluxes and DNA synthesis in vascular smooth muscle cells.

Abstract: Previous reports have suggested that phorbol esters can decrease the affinity of epidermal growth factor (EGF) for its cellular receptors. Investigations of the consequences of the interaction between phorbol esters and EGF, however, have been limited to EGFstimulated Na/H exchange in A431 cells (Whitely, B., D. Cassel, Y.-X. Zuang, and U Glaser, 1984, I. Cell Biol., 99:1162-t 166). In the present study, the effect of the phorbol ester 12-0-tetradecanoyl phorbol-13-acetate (TPA) on EGF-stimulated ion transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
3

Year Published

1986
1986
1996
1996

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 33 publications
1
29
3
Order By: Relevance
“…Furthermore, they have demonstrated that PMA-stimulated phosphorylation of an Mr 80,000 protein is attenuated upon rechallenge with phorbol ester (12)(13)(14)(15). This is consistent with other results (16)(17)(18)(19)(20)(21)(22)(23) that indicate that prior treatment with phorbol ester attenuates many PMA-induced alterations upon subsequent exposure to the tumor promoter.…”
supporting
confidence: 80%
“…Furthermore, they have demonstrated that PMA-stimulated phosphorylation of an Mr 80,000 protein is attenuated upon rechallenge with phorbol ester (12)(13)(14)(15). This is consistent with other results (16)(17)(18)(19)(20)(21)(22)(23) that indicate that prior treatment with phorbol ester attenuates many PMA-induced alterations upon subsequent exposure to the tumor promoter.…”
supporting
confidence: 80%
“…Well known targets of protein kinase C are an 80-kDa protein of unknown function (26), the epidermal growth factor receptor (27,28), and the Na+/H+ pump-either directly or indirectly (29)(30)(31)(32) (24,34), none of the aforementioned "classic" responses to protein kinase C activation has been observed (35). Nevertheless, interferon-dependent protein kinase activities have been noted with mouse 3T3-F442A and 3T3-C2 fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Na+-H+ counter-transport and sodium-dependent bicarbonate influx A Na+-H+ counter-transport which is of importance for control of pHi has been demonstrated in the smooth muscles of vas deferens (Aickin, 1984) and in cultured smooth muscle cells from aorta (Smith & Brock, 1983;Owen, 1985;Little et al 1986). In the cultured smooth muscle cells the transport was reported to be active under 'resting' conditions inasmuch as EIPA, which inhibits the Na+-H+ countertransport, added to a HEPES-buffered solution caused a gradual acidification (Weissberg et al 1987;Hatori, Fine, Nakamura, Cragoe & Aviv, 1987).…”
Section: Buffering Powermentioning
confidence: 99%
“…These results suggest that a Na+-H+ exchange and an INTRODUCTION The control of the intracellular pH (pHi) is on a short-term basis dependent on different intracellular buffers, but is on a longer-term basis dependent on the effective transport of protons over the cell membrane. A Na+-H+ counter-transport system with the potential of controlling pHi by extruding protons in exchange for Na+ moving into the cell along its electrochemical gradient has been demonstrated in many different cells (for review see Roos & Boron, 1981;Mahnensmith & Aronson, 1985) and has also recently been demonstrated in vascular smooth muscles in culture (Smith & Brock, 1983;Owen, 1985; Little, Cragoe & Bobik, 1986;Weissberg, Little, Cragoe & Bobik, 1987). A Na+-HCO3--Cl-counter-transport has also been demonstrated in different cell types mainly from invertebrates (see Boron, 1983) but also in mammalian cells including human carcinoma cells (Rothenberg, Glaser, Schlesinger & Cassel, 1983) and hamster fibroblasts (l'Allemain, Paris & Pouyssegur, 1985).…”
mentioning
confidence: 99%